RESTRICTIONS ON CONSTITUTIONAL RIGHTS IN CRIMINAL PROCEEDINGS: LEGISLATIVE REGULATION AND DOCTRINAL APPROACHES - Tarasiuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this article is to clarify the legal nature, content and limits of restrictions on constitutional rights and freedoms in criminal proceedings, as well as to formulate a scientifically based definition of this phenomenon, taking into account current legislation, the positions of scientists, the practice of the Constitutional Court of Ukraine, the European Court of Human Rights and international standards in the field of human rights. Research methods: to achieve the set goal, general scientific and special methods were used, in particular: formal-legal, systemic-structural, comparative-legal, doctrinal analysis, and analytical methods. Results: the theoretical and legal foundations for restricting constitutional rights and freedoms in criminal proceedings, particularly in cases involving procedural coercion, have been studied. It has been substantiated that restrictions on rights are an exceptional legal phenomenon that is permitted only in the presence of legal grounds, a legitimate purpose, social necessity, and compliance with the principle of proportionality. The positions of scientists regarding the nature, essence and classification of restrictions are analysed. It is established that in conditions of martial law or a state of emergency, restrictions may be broader in scope, but at the same time they must not violate the essential content of fundamental rights. The specifics of restrictions on constitutional rights, such as the right to freedom, inviolability of the home, privacy, property, movement, etc., as well as certain procedural rights of participants in criminal proceedings, are revealed. It is noted that restrictions may be imposed both in conjunction with coercive measures and independently of them in the form of procedural obligations or prohibitions. The key differences between coercion and restriction as legal phenomena are highlighted. Attention is drawn to the need for legislative regulation of the concept of restriction of rights in criminal proceedings, which will contribute to legal certainty and prevent arbitrariness. The author proposes a definition of the concept of ‘restrictions on rights and freedoms in criminal proceedings’ and formulates approaches to their classification. The need to improve procedural mechanisms for monitoring human rights compliance during criminal proceedings is justified.